(untitled) (Research, Society and Development, 2025)
Ischemic Stroke (Ischemic Stroke) is among the leading causes of death in the world. Recently, studies have linked ischemic stroke with Patent Foramen Ovale (PFO), as this relationship is common in young patients without risk factors. The foramen ovale is found in intrauterine life, with birth and the beginning of breathing, it physiologically closes. Non-closure allows the passage of emboli from the venous system to the arterial system via the right-to-left shunt, thus interrupting cerebral irrigation and reducing oxygen levels, which characterizes ischemic stroke. The study aims to describe the relationship between foramen ovale patent and ischemic stroke. Thus, this research was based on an analysis of articles selected from the VHL, PubMED, and Scielo databases, published between 2019 and 2024. The study’s initial search resulted in 163 findings, with 138 excluded for reasons such as: duplicity, not using the appropriate language or not answering the guiding question. Therefore, 25 works were selected for the production of the study. Based on the findings, a set of elements were gathered and organized according to the PRISMA criteria, producing an integrative review based on the guiding question. The research made it possible to establish the link between FOP and ischemic stroke and understand the possible forms of diagnosis. As well as understanding the anatomy and forms of treatment to prevent ischemic stroke in patients with FOP, bringing fewer risks to the health of the population.